Desarrollo del transporte urbano y su incidencia en el posicionamiento de la empresa de transportes El Cortijo S.A. en la Provincia de Trujillo, año 2019 - Núñez Mendoza, Carolina Cristina (2019)
This research was developed with the aim of demostrate that the Development of urban transport has a significant impact on the Positioning of the transport company El Cortijo S.A. after the improvement of its service, renewal of its vehicular infrastructure and customer service, led by the new requirements and regulations involved in the redesign of the urban transportation system. The research problem is referred to the following question: ¿How does urban transportation Development affect the Positioning of the transport company El Cortijo S.A in Trujillo, 2019? The population under study consist of 505,041 inhabitants of Trujillo and El Porvenir, of which a probabilistic sample of 384 users was stablished. For the present investigation the descriptive design was used, as well as the inductive and deductive method, and finally the following research techniques were applied: Indirect observation and the survey. The investigation resulted in the improvement of the service provided by El Cortijo S.A, its Positioning increases. With this research, it is concluded that the Development of urban transport has a significant impact on the Positioning of the Transport Company El Cortijo S.A.